2013
DOI: 10.1136/bjophthalmol-2013-303655
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood and ocular perfusion pressure with structural glaucomatous progression by flicker chronoscopy

Abstract: This study is the first to use structural progression and flicker chronoscopy to identify vascular glaucoma risk factors. Older age and lower diastolic BP were associated with progression. By multivariable analysis diastolic BP was associated with RNFL and neuroretinal rim loss. These findings suggest that diastolic BP is associated with structural glaucomatous progression which may have implications for management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…Systemic HT, even when treated with anti-hypertensive medications, has been shown to be a risk factor for progressive RNFL thinning in subjects with glaucoma. 21 Our findings of a higher DBP inducing greater RNFL thinning were in contrast to those reported by McGlynn et al 26 who reported that a lower DBP was associated with more progressive RNFL loss (OR = 0.2 per 10 mmHg, 95% CI 0.1–0.6, P < 0.006). As previously mentioned, from the Los Angeles Latino Eye Study, it was demonstrated that the relationship between DBP and glaucoma prevalence is in a “U-shape” signifying that extremes of DBP (too high or too low) were detrimental for glaucoma since a high DBP can cause vascular dysregulation, whereas a low DBP can result in a low ocular perfusion pressure.…”
Section: Discussioncontrasting
confidence: 99%
“…Systemic HT, even when treated with anti-hypertensive medications, has been shown to be a risk factor for progressive RNFL thinning in subjects with glaucoma. 21 Our findings of a higher DBP inducing greater RNFL thinning were in contrast to those reported by McGlynn et al 26 who reported that a lower DBP was associated with more progressive RNFL loss (OR = 0.2 per 10 mmHg, 95% CI 0.1–0.6, P < 0.006). As previously mentioned, from the Los Angeles Latino Eye Study, it was demonstrated that the relationship between DBP and glaucoma prevalence is in a “U-shape” signifying that extremes of DBP (too high or too low) were detrimental for glaucoma since a high DBP can cause vascular dysregulation, whereas a low DBP can result in a low ocular perfusion pressure.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study found that a history of systemic hypertension is not a risk factor for visual field progression, since fewer patients in the progression group had systemic hypertension. Consistent with this result, previous studies showed that a lower diastolic blood pressure was associated with glaucomatous progression [ 8 , 9 ]. Comparisons of other characteristics demonstrated that the use of β -blocker or carbonic anhydrase inhibitor eyedrops was more common in the visual field progression group.…”
Section: Discussionsupporting
confidence: 87%
“…A similar proportion of patients with RNFL progression and neuroretinal rim loss had lower diastolic blood pressure compared to those without these structural changes. This study therefore used flicker to reveal a correlation that may have significant implications for glaucoma management [23]. Similarly, Chee et al performed a study in which two glaucoma specialists assessed serial flicker chronoscopy images for features of structural progression, and found that age was significantly associated with global (OR = 1.8 per year, p \ 0.001) and PPA progression (OR = 1.7 per year, p = 0.002), and lower corneal hysteresis was associated with global progression (OR = 0.78 per mmHg, p = 0.049) and RNFL loss (OR = 0.5 per mmHg, p = 0.02) [24 • ].…”
Section: Using Automated Flicker To Identify Other Glaucoma Risk Factorsmentioning
confidence: 99%